(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
The article examines the methodological foundations of organizing distance education for students with disabilities. Key aspects such as adapted learning content, feedback, assistive technologies, and teacher preparedness are considered. It is emphasized that a comprehensive approach ensures accessibility and effectiveness of the educational process.